Arangphams, the Event Managers of the Traditional Rituals of Manipur (India): Aspects on the Management System of Local Culture - Singh, Lokendra; Rajkumari, Tamphasana (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2021)
-